FIRST DESCRIPTION OF IN SITU COSMIC SPHERULES IN FERROMANGANESE CRUST FROM THE ALBA GUYOT (MAGELLAN SEAMOUNTS) - Savelyeva, O.L.; Savelyev, D.P.; Zobenko, O.A.; Rashidov, V.A. (Vestnik Kamčatskoj regionalʹnoj associacii "Učebno-naučnyj centr". Seriâ: Nauki o Zemle (Online), 2024)
Nine cosmic I-type spherules were found in undisturbed occurrence in polished preparations from the ferromanganese crust of the Alba guyot (Magellan Seamounts). They consist of Fe oxides and sometimes contain a core of Fe and Ni alloy. The spherules are 40–250 μm in size. The spherules are in porous phosphatic clay material filling the spaces between columns composed of Fe and Mn oxyhydroxides. Phosphates in the matrix containing the spherules are mainly represented by bone debris. Barite grains, zeolites, and foraminifers were found. The presence of spherules in situ in the Fe-Mn crust excludes contamination during sample preparation and indicates that the spherules accumulated almost simultaneously with the host layer. Spherules from crushed crusts of Alba and Fedorov guyots were also studied; the presence of a ferromanganese shell with a concentric-layered structure was noted in some of them.